The Witch’s Flight: The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara (Duke University Press, 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anticapitalist Black Liberation movements based in the United States. Drawing on Gilles Deleuze’s notion of “the cinematic”—not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself —Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé